Monotonic and cyclic oedometer tests on sand at high stress levels - Uygar, E; Doven, AG (Springer, 2006)
In this paper, one-dimensional compression behavior of uniformly graded fine sand is studied with the use of oedometer test at elevated stress levels. To reach the elevated stress levels, testing is performed in a strain controlled manner. In addition, standard stress controlled testing method is also used at lower stress levels for the purpose of comparison. Specimens prepared with initial relative densities ranging from loose to dense are subjected to normal loading as well as hysteretic and repeated loading patterns. Results showed that there is a linear relationship between compressibility index and relative density. The magnitude of compression is mainly influenced by inundation where the compressibility behavior is found to be depending on the initial formation density. Regardless of the initial formation density, convergence to a similar compression index is observed with the hysteretically loaded samples whereas a continuous modification was obtained with repetitively loaded reformed specimens.
Keywords: sand; compression behavior; hysteretic loading; repeatitive loading; particle crushing